Cyclin K dependent regulation of Aurora B affects apoptosisand proliferation by induction of mitotic catastrophe inprostate cancer - Schecher, Sabrina; Walter, Britta; Falkenstein, Michael; Macher-Göppinger, Stephan; Hadaschik, Boris; Duensing, Stefan; Roth, Wilfried; Tagscherer, Katrin (International journal of cancer, 2017)
Cyclin K plays a critical role in transcriptional regulation as well as cell development. However, the role of Cyclin K in prostatecancer is unknown. Here, we describe the impact of Cyclin K on prostate cancer cells and examine the clinical relevance ofCyclin K as a biomarker for patients with prostate cancer. We show that Cyclin K depletion in prostate cancer cells inducesapoptosis and inhibits proliferation accompanied by an accumulation of cells in the G2/M phase. Moreover, knockdown ofCyclin K causes mitotic catastrophe displayed by multinucleation and spindle multipolarity. Furthermore, we demonstrate aCyclin K dependent regulation of the mitotic kinase Aurora B and provide evidence for an Aurora B dependent induction ofmitotic catastrophe. In addition, we show that Cyclin K expression is associated with poor biochemical recurrence-free survivalin patients with prostate cancer treated with an adjuvant therapy. In conclusion, targeting Cyclin K represents a novel, promis-ing anti-cancer strategy to induce cell cycle arrest and apoptotic cell death through induction of mitotic catastrophe in pros-tate cancer cells. Moreover, our results indicate that Cyclin K is a putative predictive biomarker for clinical outcome andtherapy response for patients with prostate cancer.